2010
DOI: 10.1108/00330331011064221
|View full text |Cite
|
Sign up to set email alerts
|

The state of development of digital libraries in Poland

Abstract: Purpose -The purpose of this paper is to describe the state of development of Polish digital libraries. Design/methodology/approach -The paper describes the establishment of the first digital library in Poland, the creation of the Wielkopolska Digital Library and other regional digital libraries. The organisational and technological solutions used by these libraries are described. Findings -The concept of a single central library and several dozen regional libraries has made possible the creation of more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Yakel (2007) explained that librarians with sufficient digital skills will remain successful and relevant in working with modern information systems. Gorny et al (2010) were alarmed that librarians, who are not technically skilled, should perceive digital libraries as a threat to their employment.…”
Section: Introductionmentioning
confidence: 99%
“…Yakel (2007) explained that librarians with sufficient digital skills will remain successful and relevant in working with modern information systems. Gorny et al (2010) were alarmed that librarians, who are not technically skilled, should perceive digital libraries as a threat to their employment.…”
Section: Introductionmentioning
confidence: 99%
“…This also indicates that all of the students, teachers, and experts considered that the presentation and design of DL user interfaces are what users have contact with in the very beginning, and they are important factors in the quality of user interfaces. DLs should meet users' fundamental needs (Górny et al, 2010). The interfaces should be easy to use, the language should be understood by users, and the searching function should be convenient and reliable (Hariri and Norouzi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Do (2014) and Nguyen (2017) identified a gap between theory and practice in the Library and Information Management field in Vietnam, in other words between what is taught in universities and what is required in practice. Therefore, Gorny et al (2010) alarmed that librarians who are not technically skilled should perceive digital libraries as a threat to their employment. This may be why, Raju (2014) concluded that librarians must possess knowledge of digitization, metadata creation and management, preservation of digital information and computer skills, which are useful to work in online information environments.…”
Section: Evaluation Of Digital Library Educationmentioning
confidence: 99%